2011
DOI: 10.4093/dmj.2011.35.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Triglyceride Is Associated with Fasting Triglyceride and HOMA-IR in Korean Subjects with Type 2 Diabetes

Abstract: Background: Recent studies indicate postprandial triglyceride (TG) had a better association with cardiovascular events and metabolic syndrome than fasting TG. The authors of the present study investigated the metabolic and clinical relevance of postprandial TG. Methods: In a cross-sectional retrospective study, the authors of the present study compared fasting and postprandial TG and analyzed the relationship between postprandial TG and various demographic and metabolic parameters in 639 Korean subjects with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We analyzed 361 newly diagnosed type 2 diabetes patients who were drug‐naïve, and had undergone a mixed meal test between June 2009 and April 2011. These participants included most of the patients described in our previous study. The test was a standardized liquid meal test (Ensure; Meiji Dairies Corporation, Tokyo, Japan; 500 kcal, 17.5 g fat [31.5%], 68.5 g carbohydrate [54.5%] and 17.5 g protein [14.0%]) after overnight fasting.…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed 361 newly diagnosed type 2 diabetes patients who were drug‐naïve, and had undergone a mixed meal test between June 2009 and April 2011. These participants included most of the patients described in our previous study. The test was a standardized liquid meal test (Ensure; Meiji Dairies Corporation, Tokyo, Japan; 500 kcal, 17.5 g fat [31.5%], 68.5 g carbohydrate [54.5%] and 17.5 g protein [14.0%]) after overnight fasting.…”
Section: Methodsmentioning
confidence: 99%
“…The most interesting finding we observed one month after the treatment was a significant increase in serum triglyceride levels in patients with successfully eradicated H.pylori who received standard triple therapy; while no similar adverse effect was observed in patients who were treated alternatively with BSP, or received BSP as complementary treatment of standard triple therapy. Serum triglycerides have been identified as major contributing factor and independent predictor of coronary heart disease in patients with type 2 diabetes, and lowering triglyceride levels has always considered a main clinical target in these patients [ 18 ]; it has been suggested that even a temporary and short-term increase in triglyceride levels could be accompanied by development of insulin resistance, endothelial damage and dysfunction, especially in patients with diabetes, via increased levels of intracellular adhesion molecule-1, vascular cell adhesion molecule-1, and E-selectin, as well as oxidative stress [ 19 - 21 ]. Another important risk factor outcome observed following the H.pylori eradication was clinically considerable, but not statistically significant, elevated triglyceride to HDL-C ratio in the STT group; TG/HDL-C ratio is a main atherogenic lipid parameter that is directly related to lipoprotein particle size and especially small LDL-dense particles in the plasma [ 22 , 23 ]; patients with type 2 diabetes with high TG/HDL-C ratio are potentially at a higher risk for increased arterial stiffness and atherosclerosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 In fact, several studies have demonstrated that fed state blood glucose and triglycerides values are more strongly associated with all-cause CV morbidity and mortality. 16 The OMTT, besides allowing the study of postprandial metabolism, is a closer approach, than oral glucose tolerance tests, to the actual food ingestion as the nutritional supplement contains proteins, carbohydrate and fats, rather than pure glucose.…”
Section: Discussionmentioning
confidence: 99%